Dampak Bullying terhadap Kesehatan Mental Anak SDN 1 Demak Ijo - Anis Khoirunnisa; Putri Zudhah Ferryka; Nela Rofisian (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to (1) determine the factors that cause bullying at SDN 1 Demak Ijo. (2) to determine the impact of bullying on the mental health of children at SDN 1 Demak Ijo. This research is qualitative research. This research was carried out at SDN 1 Demak Ijo. The research was carried out over a period of 3 months starting from April to June 2024. To find data, researchers used observation, interviews and documentation techniques. The data source was obtained from the class 3 homeroom teacher, 1 perpetrator and 1 victim. The results of the research show that: (1) the factors causing bullying at SDN 1 Demak Ijo are lack of empathy, inability to manage emotions, tendency towards group conformity, feelings of inferiority or insecurity, wrong understanding of power and control, negative behavior models, indifference towards impact of behavior and problems in personal life. (2) The impact of bullying behavior on the mental health of children at SDN 1 Demak Ijo, namely anxiety, silence, lack of self-confidence when carrying out school activities, weakness, fear of meeting the perpetrator and becoming gloomy.